2021
DOI: 10.3389/fneur.2021.640137
|View full text |Cite
|
Sign up to set email alerts
|

Screen Fast, Screen Faster: A Pilot Study to Screen for Depressive Symptoms Using the Beck Depression Inventory Fast Screen in Parkinson's Disease With Mild Cognitive Impairment

Abstract: Objective: Depressive symptoms have a high prevalence in patients with Parkinson's disease (PD) and are associated with cognitive dysfunction. Especially in PD with mild cognitive impairment (MCI), a time-efficient and valid instrument for the assessment of depression primarily focusing on psychological symptoms and disregarding confounding somatic symptoms is needed. We performed an examination of the psychometric properties of the Beck Depression Inventory II (BDI-II) and the Beck Depression Inventory Fast S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 27 publications
(15 reference statements)
0
8
0
Order By: Relevance
“…A cutoff ≥ 6 indicates functional impairment. The BDI-FS is self-report seven-item questionnaire assessed on a four-point scale (no symptoms to severe symptoms) [ 21 ]. Total score ranges from 0 to 21 with a cutoff ≥ 4 indicating the presence of depressive symptoms.…”
Section: Methodsmentioning
confidence: 99%
“…A cutoff ≥ 6 indicates functional impairment. The BDI-FS is self-report seven-item questionnaire assessed on a four-point scale (no symptoms to severe symptoms) [ 21 ]. Total score ranges from 0 to 21 with a cutoff ≥ 4 indicating the presence of depressive symptoms.…”
Section: Methodsmentioning
confidence: 99%
“…(Beck et al, 2000). It has been shown to be reliable and valid with diverse health conditions and a general community sample (Elben et al, 2021, Kliem et al, 2014. Kliem et al (2014) reported a Cronbach's α of 0.84..…”
Section: Beck Depression Inventory -Ii Fast Screen (Bdi-fs) the Bdi-f...mentioning
confidence: 99%
“…This brief self-report inventory comprising seven items is used to evaluate depression in patients whose behavioral and somatic symptoms attributable to medical problems may confound diagnosis. This instrument has been found to have good psychometric properties and its use in screening PD patients has been encouraged [17]. The BDI-FS replaced the BDI-II as the depression instrument halfway through the data collection.…”
Section: Methodsmentioning
confidence: 99%